PERAN PESANTREN SEBAGAI PENGGERAK EKONOMI MASYARAKAT KADEMANGAN KOTA PROBOLINGGO - Pri Astutik, Imama; Mariyatul Kifiyah, Sarifah; Alvina, Tahta; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2025)
This study explores the role of Islamic boarding schools (pesantren) as drivers of community economic empowerment in Kademangan District, Probolinggo City, by examining their educational, institutional, and collaborative functions. The scope of the study covers how pesantren foster economic independence through entrepreneurship education and training, the development of Sharia-based cooperatives and business units, and partnerships with local government and business actors. The aim is to analyze the contribution of pesantren to improving community welfare and to identify enabling and constraining factors that influence the optimization of their economic role. This research employs a qualitative descriptive-analytical approach using library research, based on a critical review of relevant journals, books, and empirical reports. The findings indicate that pesantren possess strong social, spiritual, and community capital that can be transformed into Islamic value-based economic power, provided it is managed professionally, transparently, and collaboratively. The study concludes that pesantren have the potential to become strategic socio-economic transformation agents at the local level, as long as they are supported by inclusive public policies, strengthened managerial capacity, and sustainable synergy with key stakeholders.